William Shakespeare's tragedy of the Sith's revenge : Star Wars part the third - Doescher, Ian (Star wars, 2015)
A tongue-in-cheek conclusion to the best-selling series that adapts Star Wars scripts in Shakespeare's iambic pentameter augments the story of the fall of the house of Skywalker with stirring soliloquies, inside jokes and Elizabethan-style illustrations.